A vibration analysis used in the methods of detecting unsteady operational modes of axial compressors - Чигрин, Валентин Семенович; Епифанов, Сергей Валерьевич; Мохаммадсадеги, Фаррох (Eastern-European Journal of Enterprise Technologies, 2015)
We have grounded the necessity to devise a system of a compressor surge prevention at the stage of its inception and analysed possible informative parameters characterizing an unsteady flow in a compressor and the possibility of a surge. We have presented the results of numerical simulation of the flow and dynamics of the loss of gas-dynamic stability in the inter-blade channel of the axial compressor impeller. It has been determined that the process of the loss of dynamic stability begins with the appearance of the initial vortex zone on the back of the blade profile. We have carried out an experimental research with measuring the pressure pulsation and vibration, revealed that the levels of pressure fluctuations on the impeller with a frequency of rotor blades can signal of the compressor stall, and pointed out the problems of technical use of this criterion. We have experimentally researched the connection of unstable flows in the flow part and vibration levels in the compressor housing. It is proved that the harmonics of the rotating stall that is determined by the level of vibrations is stable and significantly stands out from the background noise, so it can be used to diagnose the rotating stall as a signal of the surge. The paper contains an experimentally verified dependence for determining the frequency of the rotating stall. We have studied the possibility of using the median and band filters in processing the vibrations and suggested an algorithm for identifying a pre-surge compressor state by the rate of vibrations in the compressor housing, which is aimed at devising of automatic warning systems for the surge prevention at the stage of its inception. Devising a system of an anti-surge protection with the use of the vibration signal would increase the reliability of its work and raise the operational reliability of a gas turbine engine by eliminating false positives.